Border Sanctuary : The Conservation Legacy of the Santa Ana Land Grant - Morgan, M. J., 1955- (Book collections on Project MUSE., 2015)
The Santa Ana National Wildlife Refuge lies on the northern bank of the Rio Grande in South Texas, about seventy miles upriver from the Gulf of Mexico. In Border Sanctuary, M.J. Morgan uncovers how 2,000 acres of rare subtropical riparian forest came to be preserved in a region otherwise dramatically altered by human habitation. The story she tells begins and ends with the efforts of the Rio Grande Nature Club to protect one of the last remaining stopovers for birds migrating north from Central and South America. In between, she reconstructs a hundred-year human and environmental history of th.